INFLUENCES OF INTERNAL ENVIRONMENT, EXTERNAL ENVIRONMENT, BUSINESS ETHICS AND ENTREPRENEURSHIP TOWARD BUSINESS PERFORMANCES THROUGH DIFFERENTIATION STRATEGIES AND COMPETING SUPERIORITIES IN SMALL INDUSTRIES IN SURABAYA CITY: INFLUENCES OF INTERNAL ENVIRONMENT, EXTERNAL ENVIRONMENT, BUSINESS ETHICS AND ENTREPRENEURSHIP TOWARD BUSINESS PERFORMANCES THROUGH DIFFERENTIATION STRATEGIES AND COMPETING SUPERIORITIES IN SMALL INDUSTRIES - Tengtarto, Jaya Adi Gama (Archives of Business Research, 2020)
The purpose of this study is to examine and analyze the influence of: (1) internal environment, external environment, business ethics, entrepreneurial orientation on differentiation strategies; (2) internal environment, external environment, business ethics, entrepreneurial orientation, differentiation strategies on competitive advantage; (3) internal environment, external environment, business ethics, entrepreneurial orientation, differentiation strategies, competitive advantage on business performance. This research is an explanatory type of research with a quantitative approach. The populations in this study were all Small Industries in Surabaya as many as 384 Small Industries in Surabaya, while the samples used were 349 Small Industries in Surabaya. Data collection is done by questionnaire. The data analysis technique used is the Structural Equation Model (SEM) with AMOS program. Based on the results of the analysis shows that: (1) internal environment, external environment, business ethics, entrepreneurial orientation significantly influences on differentiation strategy; (2) business ethics, entrepreneurial orientation, differentiation strategy has a significant influences on competitive advantage, while internal environment and external environment does not have a significant influences on competitive advantage; (3) internal environment, entrepreneurial orientation, differentiation strategies, competitive advantage has a significant influences on the performance of small industries, while external environment and business ethics has no significant influences on the performance of small industries.